Exploring the adaptive leisure activities of classified nursing model in elderly colon cancer patients: a perspective on interactive care - Yun-Zhao Lin; Po Chen; Meng-Meng Lin; Jia-Li Chen; Min-Min Shi; Feng Guo (BMC Palliative Care, 2023)
Abstract Objective The aims of the study were first to explore the adaptive leisure activities of classified nursing model from the perspective of nurse-patient interactive care, and to explore its impact on the physical and mental health of patients with colon cancer. Methods From September 2017 to March 2022 as the observation time node, 82 patients with colon cancer who met the established inclusion and exclusion criteria were regarded as the research objects through the random number table as the grouping tool. The two groups of patients were named as the research group and the control group, with 41 patients in each group. The control group implemented routine nursing measures, and the research group implemented classified nursing mode and adaptive leisure activity mode. The two groups of patients received 4 weeks of nursing intervention. With the help of self-rating anxiety scale, self-rating depression scale, self-care ability evaluation scale and health status survey brief form, the two groups of patients were compared before intervention and at the end of the 4th week after intervention. Results After the intervention, the anxiety score (t = 6.656, p < 0.001) and depression score (t = 4.851, p < 0.001) of the research group were lower than those of the control group, and the difference was statistically significant. After the intervention, the self-concept (t = 4.845, p < 0.001), self-responsibility (t = 6.071, p < 0.001), self-care skills (t = 3.341, p < 0.001), health knowledge (t = 3.698, p < 0.001) and total score (t = 9.246, p < 0.001) of the research group were higher than those of the control group, and the difference was statistically significant. After the intervention, physical functioning (t = 8.141, p < 0.001), bodily pain (t = 6.083, p < 0.001), general health (t = 9.424, p < 0.001), role-physical (t = 8.057, p < 0.001), role-emotional (t = 13.252, p < 0.001), mental health (t = 12.565, p < 0.001), social functioning (t = 10.813, p < 0.001) and vitality score (t = 12.890, p < 0.001) of the research group were higher than those of the control group, with significant differences. Conclusion Interactive care through adaptive leisure nursing improves mental well-being, self-management, and psychosocial functioning in elderly colon cancer patients, promoting overall health.